2012
DOI: 10.1021/ie302853r
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Reversible Oligomerization of l-Lactic Acid with a SnCl2·2H2O/p-Toluenesulfonic Acid Catalyst

Abstract: An experimental and theoretical modeling study is presented on the kinetics of reversible oligomerization of L-lactic acid and the formation of L-lactide in closed reactors with SnCl 2 •2H 2 O/p-toluenesulfonic acid as a binary catalyst mixture. The experimental data and model simulations indicate that about 10 wt % L-lactide is produced by the cyclization of two repeating units of poly(L-lactic acid) at the chain end during the oligomerization process. The effects of the catalyst and reaction temperature at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
(41 reference statements)
1
7
0
Order By: Relevance
“…Baick et al reported the reversible oligomerization of L-lactic acid in this binary catalyst system [24]. Miao et al applied this binary catalyst method to the synthesis of PLA-PEG-PLA triblock copolymers [25].…”
Section: Racemizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Baick et al reported the reversible oligomerization of L-lactic acid in this binary catalyst system [24]. Miao et al applied this binary catalyst method to the synthesis of PLA-PEG-PLA triblock copolymers [25].…”
Section: Racemizationmentioning
confidence: 99%
“…Miao et al applied this binary catalyst method to the synthesis of PLA-PEG-PLA triblock copolymers [25]. The reaction time, temperature, pressure and ratio of binary catalysts were studied to determine their effect on polymer decomposition, discoloring and racemization [14][15][16]24,25]. We previously reported that a reaction time longer than 20 h in melt polycondensation of PLLA was ineffective for further polymerization, but rather induced discoloration and racemization of PLLA [14].…”
Section: Racemizationmentioning
confidence: 99%
“…In the last years, medical applications of polylactic acid (PLA) have gained enormous interest due to the totally body absorbable nature of PLA. PLA can be synthesized by the melt condensation of lactic acid . Removal of water, formed by condensation reaction, from the bulk material is necessary either by evaporation under reduced pressure or by driving it away by a carrier gas (e.g., nitrogen).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, maximum number average molecular weights (MWs) have been reached after 30–90 h at 180–200°C depending on the catalyst ( M n ∼ 2,300–90,000 g mol −1 ) . The use of Sn(II) catalysts activated by sulfonic acids can increase the MW of PLA . 1,3‐propanedisulfonic acid and 1,5‐naphthalene disulfonic acid have been found to successfully synthesize high MW PLA .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation